When should antiretroviral therapy for HIV be started? - Phillips, Andrew N (BMJ Publishing Group Ltd., 2007)
Treatments for HIV have advanced rapidly over the past decade. Andrew Phillips and colleagues argue that we should re-evaluate the timing of treatment in the light of new knowledge